Formação de professores universitários: Contribuições Sociologia da Educação Crítica - Valentinuz, Susana (Universidad Nacional del Litoral, 2019)
This work is an invitation to challenge ourteaching practices that are embedded in an institutionaland socio-political context, have an epistemologicalanchorage delimited by the particular field of knowledge,and are defined by theoretical perspectives andideological-political options. One of the tasks proposedby Sociology of Education is to ask ourselves whichtraining processes are being developed by universityteachers to challenge their own trajectory and to generatecritical educators with transformative intentionality.Some discussions on this issue are shared in this article.Pedagogical training of teachers at secondary anduniversity levels is a challenge for those who have theconviction that not only disciplinary knowledge shapes the teaching practice but also a baggage of knowledgethat provides meaning to specific knowledge, makingup an integrated whole in teaching. The pedagogicaltask often seems to unfold with autonomy of ethical andpolitical principles. In addition, the ways to build teacher-students relationship in university classrooms onlycircumscribed to the ‘critical contents’ of the subjectswithout an appropriation anchored in the experienceof an alternative pedagogical practice runs the risk oflosing precisely its transforming potential.